(untitled) (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
Over the last decades, a demystification of the image of the labyrinth has been observed in a remarkable way within the modern literary field. Several writers from the contemporary French-speaking space have taken up, in their writings, the theme of the labyrinth, including Rachid Boudjedra who proposed, on several levels, to nourish his novel Topographie idéale « pour une agression caractérisée » of this theme. This article aims to see the way in which the image of the labyrinth is deployed within this novel. A key concept is put at the service of our analysis: « hybridity ». Reflection on this concept thus allows us to conceive the image of the labyrinth as a kaleidoscopic image, set up by Boudjedra not only to emphasize the sinuosity of the space in which the character wanders but also to show that the labyrinth can be a motif likely to bring out, within the fictional universe, a new space loaded with several meanings.